Pengaruh Kualitas Pelayanan Dan Fasilitas Wisata Terhadap Kepuasan Wisatawan Nusantara Yang Berkunjung Ke Pura Luhur Uluwatu - Sari, Harum Puspita; Sagita, Putu Agus Wikanatha; Dewi, Luh Gede Leli Kusuma (JURNAL DESTINASI PARIWISATA; Vol 12 No 2 (2024): VOL 12, NO 2 (2024): (JULY-DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2024.v12.i02.p17, 2024)
This study aims to evaluate the impact of service quality and tourism facilities on the satisfaction of domestic tourists visiting Uluwatu Temple. Employing a quantitative research method with data collection through questionnaires, this research focuses on analyzing tourists' perceptions of the services and facilities provided at Uluwatu Temple. The findings of this study can provide a significant contribution to the Indonesian tourism industry, particularly in understanding the factors influencing tourist satisfaction. The data analysis results indicate that both service quality and tourism facilities have a significant partial and simultaneous impact on the satisfaction levels of domestic tourists. Factors such as staff friendliness, cleanliness, and the availability of common facilities play a crucial role in shaping a positive tourist experience. Consequently, Uluwatu Temple needs to continually improve its service and facility standards to maintain and enhance its appeal to tourists. This research is expected to guide tourism destination managers in developing more effective strategies to enhance tourist satisfaction and promote sustainable domestic tourism growth. Keywords: service quality, facilities, tourist satisfaction